The Effect of Partial Wheat Flour Substitution by Unripe Banana Flour and Particle Sizes on the Physical, Chemical Properties and In Vitro Digestibility of Instant Noodles - Chintong, Sutasinee; pandolsook, sawanya (Journal of Food Technology, Siam University, 2022)
The objective of the study was to develop instant noodles with functional properties by partial wheat flour substitution with unripe banana flour. The study was undertaken to show the extent of improvement based on the size counterparts of the flour. The effect of addition of mechanically fractionated flours (fine fraction; 80 mm and coarse fraction; 250 mm) from unripe banana flour as a partial substitute (0%, 10%, 20%, and 30%) for wheat flour on the physical, chemical and in vitro digestibility properties was investigated. The results indicated that use of unripe banana flour at 30% substitution level significantly decreased the oil content and energy caloric value and increased the moisture and fiber (p<0.05). As the amount of banana flour increased, the appearance became darker and the stickiness of the noodles decreased when compared to the control sample. Addition of 30% coarse banana flour resulted in a marked increase in resistant and slow digestible starch levels in the instant noodles. Despite the change in color and texture of the product it presented, the digestibility of the instant noodle samples showed that unripe banana flour produced from a mechanical fractionation can be used as a promising functional ingredient to prepare instant noodles with greater nutritional value prospects.